The resurrection of the genus Bergia (Anthozoa, Zoantharia, Parazoanthidae). Issue 1 (2nd January 2016) - Montenegro, Javier; Low, Martyn E. Y.; Reimer, James Davis
Abstract : The genus Bergia was established by Duchassaing de Fonbressin and Michelotti in 1860, for two species, Bergia catelunaris and B. vialactea . Subsequently, in 1903 Duerden recognized these two species as conspecific, and used B. catelunaris in favour of B. vialactea, and transferred B. catelunaris to the genus Parazoanthus . However, over the last decade, it has been found that the genus Parazoanthus is actually polyphyletic and therefore it has gradually been divided and redefined. Based on phylogenetic analyses, Parazoanthus sensu stricto was recently limited to species which form associations with sponges, but it still comprised of three distinctive and monophyletic subclades. Of these clades, one Parazoanthus clade contains the type species for Parazoanthus, P. axinellae, while another clade was recently described as the genus Umimayanthus based on mitochondrial 16S-rDNA sequences. However, the other remaining Parazoanthus clade contains P. catenularis, the original type species of the genus Bergia . Based on a concatenated set of published data for five molecular markers (18S-rDNA, 28S-rDNA, ITS1/5.8S/ITS2-rDNA, 16S-rDNA and COI-DNA), this study confirms the monophyly of Bergia in the context of Parazoanthidae. The phylogenetic analyses strongly support the resurrection of the genus Bergia as a valid taxonomic unit.